-1/w-2=-4+3/w-1

Simple and best practice solution for -1/w-2=-4+3/w-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1/w-2=-4+3/w-1 equation:



-1/w-2=-4+3/w-1
We move all terms to the left:
-1/w-2-(-4+3/w-1)=0
Domain of the equation: w!=0
w∈R
Domain of the equation: w-1)!=0
w∈R
We add all the numbers together, and all the variables
-1/w-(3/w-5)-2=0
We get rid of parentheses
-1/w-3/w+5-2=0
We multiply all the terms by the denominator
5*w-2*w-1-3=0
We add all the numbers together, and all the variables
3w-4=0
We move all terms containing w to the left, all other terms to the right
3w=4
w=4/3
w=1+1/3

See similar equations:

| -12x+3(x-5)+7x=6x-63 | | X-1/2a=0 | | x^2-200*x-500=0 | | 2(5-6r)=10r-188 | | 9n+2=31 | | 3.5(t+6)=7 | | -3p-3(6-4p)=6(p-2)-15 | | 3.5y=15 | | 7/x+3=5/x+11 | | 2/3(3x-12)=3/4(4x-3) | | -13=-p | | 6y-10=6y+10=180 | | 0.8(v-7)=2 | | 24-3(6-3x)=11/4x | | s-10=4 | | -12x+2(x-4)+9x=9x-58 | | 2(m+3)/3=6m+2 | | (x-2)^2+17=17 | | 2(x+3)+6=3x-9 | | (2/7)x-2=x-(1/2) | | q+-2=-6 | | -3x+5x-16=2(x-3)-26 | | y=-12=18 | | 4/5(v-7)=2 | | 2(x+1)-3=6x+1-4x | | -28-6x+3x=14 | | (x-2)^2+17=0 | | -5.5(d-2)=-12.1 | | 6x–2(x+4)=12 | | 3x+0.25x=14.25 | | y+8=-1 | | X^2-22x+121=4 |

Equations solver categories